Dynamic and Mathematical Models of Motion "Legs", Upper Rack of the Mechanism Fabric Transportation of Sewing Machines - Bozorova Farida Maxmudjonovna (International Journal on Orange Technologies, 2021)
The article provides a constructive scheme and principles of operation of a self adjusting foot for manufacturing high-quality garments in sewing machines.